-28p-6(3-6p)=6(p-4)-2

Simple and best practice solution for -28p-6(3-6p)=6(p-4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28p-6(3-6p)=6(p-4)-2 equation:


Simplifying
-28p + -6(3 + -6p) = 6(p + -4) + -2
-28p + (3 * -6 + -6p * -6) = 6(p + -4) + -2
-28p + (-18 + 36p) = 6(p + -4) + -2

Reorder the terms:
-18 + -28p + 36p = 6(p + -4) + -2

Combine like terms: -28p + 36p = 8p
-18 + 8p = 6(p + -4) + -2

Reorder the terms:
-18 + 8p = 6(-4 + p) + -2
-18 + 8p = (-4 * 6 + p * 6) + -2
-18 + 8p = (-24 + 6p) + -2

Reorder the terms:
-18 + 8p = -24 + -2 + 6p

Combine like terms: -24 + -2 = -26
-18 + 8p = -26 + 6p

Solving
-18 + 8p = -26 + 6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6p' to each side of the equation.
-18 + 8p + -6p = -26 + 6p + -6p

Combine like terms: 8p + -6p = 2p
-18 + 2p = -26 + 6p + -6p

Combine like terms: 6p + -6p = 0
-18 + 2p = -26 + 0
-18 + 2p = -26

Add '18' to each side of the equation.
-18 + 18 + 2p = -26 + 18

Combine like terms: -18 + 18 = 0
0 + 2p = -26 + 18
2p = -26 + 18

Combine like terms: -26 + 18 = -8
2p = -8

Divide each side by '2'.
p = -4

Simplifying
p = -4

See similar equations:

| 400x-100(30-x)=0 | | 8x^2-7x+4=-3x+2 | | 3x+41-6x=2-9x+3 | | t+23=15 | | 48(b+12)=63+56b | | x+.40=4 | | =3(2y+4)7-30 | | 2x-3(1-3x)=10 | | 4t^3-27t^2+60t-45=0 | | 10u-98=3u | | -9(v+2)+3v+7=8v+7 | | 10-98=3u | | -5z=11-6z | | 4x^2-9x-33=0 | | x^2+3x+8=-4x-2 | | 7-4x=3l | | 105=(2x-11) | | M+18=36 | | x^2-x+4=6 | | 7x(6+9x)-2x(8+5x)= | | h=300+3.5h | | -5=c/4/3 | | -3d+7=1-5d | | 4t^3-9t^2+60t-45=0 | | (x+8)+4=x+(8+4) | | 6x-5=3x+10 | | -3x-47=73-8x | | -4x^2+2=-3x | | 9(x+7)-(8x+4)=-9 | | n^2-3n-18=11 | | (3d-12)(10-5d)=0 | | -0.66666y=5 |

Equations solver categories